2009
DOI: 10.2353/ajpath.2009.080780
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Liver Type Fatty Acid Binding Protein Accurately Reflects the Degree of Tubulointerstitial Damage

Abstract: To investigate the relationship between liver-type fatty acid-binding protein (L-FABP), a biomarker of chronic kidney disease, in the kidney and the degree of tubulointerstitial damage, folic acid (FA)-induced nephropathy was studied in a mouse model system. As renal L-FABP is not expressed in wild-type mice, human L-FABP (hL-FABP) transgenic mice were used in this study. hL-FABP is expressed in the renal proximal tubules of the transgenic mice that were injected intraperitoneally with FA in NaHCO 3 (the FA gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 34 publications
2
64
0
3
Order By: Relevance
“…An indirect immunoperoxidase method was used to identify the antigens, as described previously. 11,12 Macrophages were identified using the rat monoclonal antibody F4/80 (BMA Biomedicals, Augst, Switzerland), and type I or type III collagens were identified using rabbit polyclonal antibodies (Cedarlane Laboratories). Ten nonoverlapping fields from both the cortical and medullary areas were selected.…”
Section: Immunohistological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect immunoperoxidase method was used to identify the antigens, as described previously. 11,12 Macrophages were identified using the rat monoclonal antibody F4/80 (BMA Biomedicals, Augst, Switzerland), and type I or type III collagens were identified using rabbit polyclonal antibodies (Cedarlane Laboratories). Ten nonoverlapping fields from both the cortical and medullary areas were selected.…”
Section: Immunohistological Analysismentioning
confidence: 99%
“…Each degree of tubulointerstitial injury and of fibrosis were evaluated as ratios to the entire cortical or medullary area. 11,12 For glomerulosclerosis quantification, the grade of sclerosis in each glomerulus stained with periodic acidSchiff was defined as described previously.…”
Section: Renal Histological and Morphometric Analysismentioning
confidence: 99%
“…31 A number of studies have suggested a possible role for urinary FABP in clinical diagnosis of renal disease. 32 Ferguson et al have reported a substantial increment of urinary L-FABP in several etiologies of acute kidney injury (AKI) such as acute tubular necrosis, nephrotoxic exposure, and sepsis. 33 In contrast to previous studies, we did not detect high U L-FABP /Cr levels in our patients.…”
mentioning
confidence: 99%
“…26,27 Real-time quantitative PCR analysis was performed using a TaqMan StepOnePlus system (Thermo Fisher Scientific) to measure the mRNA levels of Nrf2, NAD(P)H quinone oxidoreductase-1, glutathione Stransferase μ1, glutathione S-transferase α4, monocyte chemoattractant protein-1 (MCP-1), regulated on activation, normal T cell expressed and secreted (RANTES), α-1 collagen type I and type III, human L-FABP and glyceraldehyde-3-phosphate dehydrogenase. The expression levels of these transcripts in each sample were normalized to the glyceraldehyde-3-phosphate dehydrogenase expression levels.…”
Section: Real-time Quantitative Pcr Analysismentioning
confidence: 99%
“…An indirect immunoperoxidase method was used to identify the antigens, as described previously. 26,27 Type I and type III collagens were identified using rabbit polyclonal antibodies (Cedarlane Laboratories Ltd, Burlington, ON, Canada). Macrophages were identified using a rat monoclonal antibody against F4/80 (BMA Biomedicals, Augst, Switzerland).…”
Section: Immunohistological Analysismentioning
confidence: 99%